Endovascular treatment of complex intracranial aneurysms using Acandis Acclino stents. (24th August 2016) - Brassel, Friedhelm; Grieb, Dominik; Meila, Dan; Schlunz-Hendann, Martin; Greling, Björn; Melber, Katharina
Abstract : Objective: To determine the safety and effectiveness of a new low-profile, laser-cut, closed-cell stent system in the treatment of complex intracranial aneurysms. Methods: A total number of 43 patients with complex intracranial aneurysms were treated using 60 Acandis Acclino stent systems (follow-up 2012–2016; mean 11 months). 36 patients presented with wide-necked intracranial aneurysms, dissecting aneurysms were seen in 7 patients. 39 patients received stent-assisted coiling. We analyzed demographic data and follow-up results. Results: Sixty stents were successfully deployed. In one paraophthalmic internal carotid artery aneurysm the stent could not be placed. Thirty-three wide necked aneurysms were treated by single or multiple stent-assisted coiling. Complete occlusion was achieved in 31 of those cases (94% Raymond−Roy occlusion classification, RROC 1). Two patients showed stable residual aneurysmal filling (RROC 3). In three wide-necked aneurysms, sole stenting was the preferred treatment. For dual stent-assisted procedures the kissing-Y stenting technique was successfully performed in 11 aneurysms. In all dissecting aneurysms constructive therapy with stenting and preservation of the affected parent artery was achieved. Additional subsequent coil embolization was intentionally planned and successfully performed in 6 of the 7 dissecting aneurysms. The overall directly procedure-related complication rate was 7%, including one death. Conclusions: Endovascular treatment of complex intracranial aneurysms using Acclino stents is a feasible and safe procedure with low complication rates. Even severe cases can be treated among others using the kissing-Y stenting technique, with good mid-term results.